Tracking the time course of object categorization using event-related potentials - Tanaka, James W.; Luu, Phan; Weisbrod, Matthias; Kiefer, Markus (Neuroreport, 1999)
Object categorization processes were investigated by measuring event-related potentials while subjects categorized objects at the superordinate (e.g. animal), basic (e.g. dog) and subordinate (e.g. beagle) levels of abstraction. An enhanced negative deflection (N1) was found at posterior recording sites for subordinate level categorizations compared with basic level categorizations and was interpreted as a marker of increased visual analysis. In contrast, superordinate level categorizations produced a larger frontal negativity relative to basic level categorizations and were interpreted as an indicator of increased semantic processing. These results suggest a neurophysiological basis for the separate cognitive processes responsible for subordinate and superordinate object categorizations.
Gesehen am 08.06.2021